2023
DOI: 10.3390/sym15091704
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Asymmetry in the Distribution of Galaxy Spin Directions—Analysis and Reproduction

Lior Shamir

Abstract: Recent independent observations using several different telescope systems and analysis methods have provided evidence of parity violation between the numbers of galaxies that spin in opposite directions. On the other hand, other studies argue that no parity violation can be identified. This paper provides detailed analysis, statistical inference, and reproduction of previous reports that show no preferred spin direction. Code and data used for the reproduction are publicly available. The results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 178 publications
4
14
0
Order By: Relevance
“…Similarly, 6.032% were annotated as rotating counterclockwise in the original images, compared to just 5.942% of the galaxies that were annotated as rotating counterclockwise in the mirrored images, showing that 1.5% more galaxies rotate counterclockwise. As explained in Shamir (2023, the 1.5%-2.2% asymmetry is in excellent agreement with the asymmetry reported in Shamir (2020d), which was analysed using the same footprint of SDSS galaxies with Table 2 The number of galaxies rotating in opposite directions in the original and mirrored images used in Land et al (2008).…”
Section: Summary Of Experiments That Showed Random Distribution Of Sp...supporting
confidence: 85%
See 4 more Smart Citations
“…Similarly, 6.032% were annotated as rotating counterclockwise in the original images, compared to just 5.942% of the galaxies that were annotated as rotating counterclockwise in the mirrored images, showing that 1.5% more galaxies rotate counterclockwise. As explained in Shamir (2023, the 1.5%-2.2% asymmetry is in excellent agreement with the asymmetry reported in Shamir (2020d), which was analysed using the same footprint of SDSS galaxies with Table 2 The number of galaxies rotating in opposite directions in the original and mirrored images used in Land et al (2008).…”
Section: Summary Of Experiments That Showed Random Distribution Of Sp...supporting
confidence: 85%
“…More importantly, as discussed in detail in Shamir (2023), reproducing the experiment with the same data and same analysis described in Iye et al (2021) provides completely different results than the results shown by Iye et al (2021). Figure 11 shows the outcome of the experiment, showing a statistically significant dipole axis of 2.14σ formed by the galaxy spin directions.…”
Section: Summary Of Experiments That Showed Random Distribution Of Sp...mentioning
confidence: 82%
See 3 more Smart Citations